1994
DOI: 10.1103/physrevc.50.1550
|View full text |Cite
|
Sign up to set email alerts
|

Transfer reactions inS32+92,

Abstract: DifFerential cross sections for quasielastic transfer were measured for S beams bombarding Mo and Nb targets at laboratory energies of 109, 116, and 125 MeV. Distorted-wave Born approximation calculations are in good agreement with the one-nucleon transfer data at all energies.Large transfer cross sections were observed for ' Mo and Nb targets which is consistent with the large sub-barrier fusion enhancement observed in the same systems. The transfer probability for one-nucleon transfer at large reaction dista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Therefore, this state was no longer considered in the calculations. In general, both calculations reproduce adequately-well the experimental data without need for any additional normalization factor [43,[100][101][102][103]. The good agreement between experimen-TABLE II: List of the one-proton spectroscopic amplitudes for the target overlaps used in the DWBA and CCBA calculations for the reactions with the 16 O and 27 Al targets.…”
Section: Resultsmentioning
confidence: 58%
“…Therefore, this state was no longer considered in the calculations. In general, both calculations reproduce adequately-well the experimental data without need for any additional normalization factor [43,[100][101][102][103]. The good agreement between experimen-TABLE II: List of the one-proton spectroscopic amplitudes for the target overlaps used in the DWBA and CCBA calculations for the reactions with the 16 O and 27 Al targets.…”
Section: Resultsmentioning
confidence: 58%
“…Data for reactions with Mo isotopes, including this system, at energies close to the barrier, were recently measured by the SUNY group [11,12]. It was found that, in the case of two-proton stripping reactions, there is an abrupt change in slope at approximately the energy corresponding to the Coulomb barrier (E lab ≈ 117 MeV).…”
Section: Resultsmentioning
confidence: 99%
“…With these prescriptions we now calculate the transfer probability as described for structureless nuclei, by substitution of Eqs. ( 8) and ( 9) or (11) into Eq. ( 17).…”
Section: B Vibrational Nucleimentioning
confidence: 99%